Ump-Miyazu MoU Set To Boost TDM Industry - UMP, PNC
In its effort to enhance universityindustry collaboration, Universiti Malaysia Pahang (UMP) recently signed a memorandum of understanding (MoU) with Miyazu (Malaysia) Sdn Bhd to further develop the tools, dies and mould (TDM) industry in Malaysia.